Benzoic acid in some milk products from the market in the Czech Republic - A. Hejtmánková; J. Dolejšková; V. Horák; H. Dragounová; F. Louda (Czech Journal of Food Sciences, 2000)
Benzoic acid is a natural component of fermented milk products. The level of benzoic acid depends on the level of hippuric acid in used milk and on the process of dairy product manufacture, especially on the technologically used microorganisms. A hygienic limit 30 mg/kg of benzoic acid in milk products was laid down in the Czech Republic in 1997. In our study we determined the levels of benzoic acid in model yoghurts and in some milk products from Czech market. The benzoic acid content was determined by HPLC, by the use of our modification of the provisional IDF standard 139(1987). All samples of model yoghurts and all samples of milk products from the market showed levels of benzoic acid below the newly set hygienic limit. Highest level of benzoic acid was determined in the sample of white cheese (22.85 mg/kg), all other products based on white cheese showed average levels. Cottage cheese products (sample P), which belongs to the family of milk products for children, showed a very low level of benzoic acid, which is considered as a very positive result.